Penyusunan Laporan Keuangan UMKM Berdasarkan Standar Akuntansi EMKM pada UMKM Pembuatan Opak - Melanie Octavia; Natasha Natasha; Nuraini Azlin; Rizky Raditya Pratama; Riska Franita (CV. ITTC INDONESIA, 2025)
This research aims to assist MSME players in preparing financial statements based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The research subject is the Opak Factory MSME in Sei Mencirim, Medan, which has not previously implemented formal financial records. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The results showed that the preparation of financial statements in accordance with SAK EMKM includes a statement of financial position, income statement, and notes to the financial statements. This report provides a simple but comprehensive overview of business finances, which can be used to evaluate business performance and attract investors and financing parties. This research proves the importance of standardised financial records for the continuity and development of MSMEs.